PROFILE OF STUDENTS RECEIVING KIP-COLLEGE SCHOLARSHIPS IN THE PANCASILA AND CIVIC EDUCATION STUDY PROGRAM IN 2020 AT BHINNEKA PGRI UNIVERSITY - Purnamasari , Nurna Listya; Dewi lutriani, Marcella (Asosiasi Dosen Muda Indonesia, 2024)
The KIP-College scholarship program at Bhinneka PGRI University suffers from several phenomena, including high pressure to achieve academic performance and involvement in student organization activities. The scholarship is only awarded to students who have achieved a certain standard of academic achievement, so recipients must maintain their academic performance. This research was conducted at Bhinneka PGRI University, Tulungagung, East Java, using a descriptive qualitative approach. From the results of the study, students who received the KIP-College Scholarship in the 2020 Pancasila and Civic Education (PPKn) Study Program showed satisfactory academic performance, with a stable GPA value above 3.60, their academic performance significantly exceeded the campus minimum standards, and achieved significant non-academic achievements. Their activeness in various organizational activities at Bhinneka PGRI University shows their commitment to participate in the study program and university levels and take advantage of the opportunities provided by scholarships. The use of strategies such as being active in class, consistent in doing assignments, and discipline in attendance at every meeting helps students maintain and improve their GPA. In conclusion, students who received the KIP-Colege 2020 Scholarship at Bhinneka PGRI University have managed to achieve satisfactory academic and non-academic achievements, they have also carried out strategies in maintaining and stabilizing GPA values such as being active in class, consistency in doing assignments, and discipline towards attendance in every meeting. They not only perform well in their studies but also actively contribute to campus life and society as a whole.